Effect of hexagonality on the pressure-dependent lattice dynamics of 4H-SiC. (1st November 2022) - Zhang, Junran; Liang, Tao; Lu, Yunhao; Xu, Binjie; Deng, Tianqi; Zhang, Yiqiang; Zeng, Zhidan; Pi, Xiaodong; Yang, Deren; Wang, Rong
Abstract: The pressure-dependent lattice dynamics of 4H-SiC is investigated using diamond anvil cell, and compared with those of 3C- and 6H-SiC. It is found that both the zone-center longitudinal optical (LO) and transverse optical (TO) modes shift to higher frequencies with the increase of the applied pressures. This indicates that polymorph transitions are unlikely to happen under the (quasi-)hydrostatic pressure. The LO–TO splitting is described well by the cubic function with respect to the applied pressure. A decrease in the LO–TO splitting is observed above 33 GPa. The change of transverse effective charge and thus the ionic character of 4H-SiC exhibits a cubic dependence on the pressure due to the nonequivalent lattice dynamics parallel and perpendicular to the c -axis of 4H-SiC. Compared to what happens in 6H-SiC, the high pressure exerts higher effect on the ionic character of 4H-SiC because less nonequivalent bilayers are evolved. At last, the mode-Grüneisen parameters of the LO and TO modes at the Γ point are determined. Given the hexagonal lattice of 4H-SiC, the LO mode are softer than the TO mode.